Програмна система для автоматизованого планування харчування заснованого на вподобаннях користувача - Волошин, Г. А.; Коробко, В. Ю. (ХНУРЕ, 2023)
The given work is devoted to the development of a software system for automated meal planning based on user preferences. To address this issue, a personalized meal schedule is necessary to ensure proper nutrition and help users achieve their goals. The software system will create a personalized schedule based on user preferences, allowing them to choose food according to their needs. Menu will be formed by developed algorithm that support high quality and variety of food including option to track calories intake amount. This project has great potential to improve people's lives by providing better health and meeting their nutritional needs, while also reducing preparation time and allowing them to enjoy tasty and healthy food